Plastic Waste Chips For Environmentally Friendly Soil Stabilization: Experimental Study On Clay Soil Improvement Using CBR Method - Kaifan, Andrian; Irham, Irham; Aiyub, Aiyub; Gani, Fauzi A.; Munardy, Munardy; Ruhana, Ruhana (Akademi Komunitas Negeri Aceh Barat, 2025)
AbstractClay soils are widely recognized for their poor engineering characteristics, particularly their low bearing capacity and high shrink-swell potential. These limitations make them unsuitable for use as foundation material in road construction and other geotechnical applications. This study aims to evaluate the potential of plastic waste chipping as an additive to improve the geotechnical properties of clay soil. The research was conducted using the California Bearing Ratio (CBR) method to assess bearing capacity. The experimental program involved mixing clay soil—sourced from Blang Pala Village, North Aceh—with varying contents of plastic waste chips (1%, 1.5%, and 2%) and different chip sizes (0.5×0.5 cm, 0.75×0.75 cm, and 1×1 cm). A series of laboratory tests were conducted, including specific gravity, Atterberg limits, standard proctor compaction, and CBR tests in both unsoaked and soaked conditions. The results revealed that the addition of plastic waste chips consistently improved the CBR values, with the most significant enhancement observed at 2% plastic content and 1×1 cm chip size. The unsoaked and soaked CBR values increased from 6.8% to 8.1% and from 3.8% to 5.9%, respectively. These findings suggest that plastic waste chips offers a promising, sustainable construction method for enhancing the performance of clay soils while contributing to plastic waste management.AbstrakTanah lempung dikenal secara luas karena memiliki sifat-sifat teknik yang kurang baik, terutama daya dukungnya yang rendah dan potensi kembang susut yang tinggi. Keterbatasan ini menjadikan tanah lempung tidak sesuai untuk digunakan sebagai bahan dasar pondasi dalam pembangunan jalan dan aplikasi geoteknik lainnya. Penelitian ini bertujuan untuk mengevaluasi potensi cacahan limbah plastik sebagai bahan tambahan guna meningkatkan sifat geoteknik tanah lempung. Penelitian dilakukan menggunakan metode California Bearing Ratio (CBR) untuk menghitung daya dukung tanah. Penelitian ini dimulai dari pencampuran tanah lempung yang bersumber dari Desa Blang Pala, Aceh Utara dengan variasi jumlah cacahan limbah plastik (1%, 1,5%, dan 2%) dan ukuran cacahan yang berbeda (0,5×0,5 cm, 0,75×0,75 cm, dan 1×1 cm). Serangkaian uji laboratorium yang dilakukan meliputi berat jenis, batas Atterberg, uji proctor standar, dan uji CBR dalam kondisi tidak direndam dan direndam. Hasil penelitian menunjukkan bahwa penambahan cacahan limbah plastik secara konsisten meningkatkan nilai CBR, dengan peningkatan paling signifikan pada kandungan plastik 2% dan ukuran cacahan 1×1 cm. Nilai CBR tidak direndam meningkat dari 6,8% menjadi 8,1% dan nilai CBR direndam meningkat dari 3,8% menjadi 5,9%. Hasil ini menunjukkan bahwa cacahan limbah plastik merupakan metode yang menjanjikan untuk konstruksi berkelanjutan untuk meningkatkan kinerja tanah lempung sekaligus turut berkontribusi dalam pengelolaan limbah plastik.